Dermatology clinical case - Sá, Liliana (2022)
Multiple lentigines (LEOPARD) syndrome is an inherited autosomal dominant disorder. LEOPARD is an acronym for the most important features of the disease: multiple lentiginous lesions, abnormal electrocardiogram, ocular hypertelorism, pulmonary stenosis, genital and reproductive abnormalities, growth retardation, and sensorineural deafness. Herein is reported the case of a 14-year-old male who presented with short stature and alopecia. The mother, maternal grandmother, and aunts had multiple lentigines all over the body and hypoacusia. Systemic examination revealed short stature, alopecia reaching over 90% of the scalp, trachyonychia, multiple lentigines mostly scattered over the trunk, four café-au-lait spots, pectus excavatum, grade II/VI systolic heart murmur, and Tanner stage G2P1A1. The genetic study confirmed LEOPARD syndrome diagnosis. Early diagnosis is useful for prospective management of associated medical conditions and genetic counseling.